Mitigation strategies for methane emissions in ruminant livestock: a comprehensive review of current approaches and future perspectives - Malyugina, Svetlana; Holik, Simon; Horky, Pavel (Frontiers in Animal Science, 2025)
Enteric methane emissions from ruminant livestock represent a major contributor to agricultural greenhouse gases and reflect an energetic inefficiency in ruminant metabolism. This review critically evaluates current mitigation strategies aimed at reducing CH4 production in ruminants, with an emphasis on practical applicability, biological mechanisms, and integration into sustainable dairy production systems. Nutritional interventions—including tannins, saponins, essential oils, garlic compounds, seaweed (e.g., Asparagopsis), probiotics, and chemical inhibitors such as 3-nitrooxypropanol (3-NOP)—are discussed in the context of their effects on rumen microbiota, fermentation patterns, and animal productivity. Biological strategies such as archaeal-targeted vaccines, bacteriophage therapy, and microbiome engineering remain largely experimental but represent promising future directions. Genetic selection for low-emission phenotypes and improved manure management are also explored as complementary approaches to reduce emissions. Although some additives have achieved CH4 reductions of 30–50% in vivo, results vary depending on diet, dose, delivery matrix, and duration. Notably, the long-term effects on productivity, nutrient utilization, and product quality remain underexplored. Integrated strategies combining dietary, genetic, and management interventions tailored to specific production systems are likely necessary to achieve meaningful, sustained reductions in ruminant CH4 emissions.